Sociodemographic characteristics, sexual behaviour and knowledge about cervical cancer prevention as risk factors for high-risk human papillomavirus infection in Arkhangelsk, North-West Russia - Roik, Elena Evgenievna; Sharashova, Ekaterina; Kharkova, Olga Alexandrovna; Nieboer, Evert; Postoev, Vitaly Alexandrovich; Odland, Jon Øyvind (International Journal of Circumpolar Health, 2018)
Source at https://doi.org/10.1080/22423982.2018.1498681 While sociodemographic predictors of cervical cancer (CC) are well understood, predictors of high-risk (HR) human papillomavirus (HPV) infection have not been fully elucidated. This study explored the HR-HPV infection positivity in relation to sociodemographic, sexual behavior characteristics and knowledge about HPV and CC prevention among women who visited the Arkhangelsk clinical maternity hospital named after Samoylova, Russia. This cross-sectional study was conducted in the city of Arkhangelsk, Northwest Russia. Women who consulted a gynecologist for any reason between 1 January 2015 and 30 April 2015 were residents of Arkhangelsk, 25–65 years of age were included. The Mann–Whitney and Pearson’s χ2 tests were used. To determine the HR-HPV status, we used the Amplisens HPV-DNA test. We used a questionnaire to collect the information on sociodemographic factors. Logistic regression was applied. The prevalence of HR-HPV infection was 16.7% (n = 50). HR-HPV infection was more prevalent in younger women, cohabiting, nulliparae, smokers, having had over three sexual partners and early age of sexual debut. The odds of having a positive HR-HPV status increased by 25% with an annual decrease in the age of sexual debut. Moreover women with one child or more were less likely to have positive HR-HPV status.